Tectonic impact on sediment routing systems of evolving rift basins: A case study from the Cenozoic Kerimbas Graben, offshore northern Mozambique - Eberts, Andreas; Kaufmann, Dirk; Stollhofen, Harald; Franke, Dieter (17th Symposium of Tectonics, Structural Geology and Crystalline Geology (TSK), 2018)
Knowledge of the submarine channel architecture and of related tectonosedimentary processes is crucial to assess sediment influx and to locate potential hydrocarbon reservoirs. Such systems are highly sensitive to changes of seabed topography, often strongly linked to tectonic uplift, faulting and seismicity. To reveal the impact of tectonic activity on channel pathways, we carried out a morphotectonic analysis of the Kerimbas Graben, an active rift basin situated in the Mozambique Channel. This area is highly influenced by the Cenozoic to recent tectonic evolution of the East African Rift System. Three high-quality geophysical datasets including high-resolution bathymetric, multichannel reflection seismic and Parasound data were acquired during two cruises of the research vessel SONNE in early 2014. By combining these datasets, we were able to map the lateral and vertical extent of topographic features such as fault scarps and channel incisions, and to interpret them in terms of their relation to tectonic activity. Our results show that the study area is divided into two distinct parts, comprising differences in both morphotectonic characteristics and in the evolution of channel pathways. The northern part, occupied by the Kerimbas Graben, shows N-S trending fault scarps the most pronounced of which are associated with the eastern and western border faults of the rift basin. Farther south, an area of “diffuse extension” is accompanied by horst-and-graben structures, acting as right-stepping transfer zones for the southward impinging eastern border fault. The observed spatial variations are also represented by differences in fault throw, revealing that fault scarps in the southern part of the study area show significantly lower vertical offsets. By assuming a roughly coherent age of the corresponding faults this suggests higher uplift rates in the Kerimbas Graben area, which in turn would imply differences in the impact of tectonics on sediment routing systems along strike of the rift. Concerning this, two basic types of interactions in the downstream parts of submarine channel systems can be inferred: (1) a complete blocking of the channel pathway occurred in areas where the rate of rift shoulder uplift exceeded the rate of channel incision. Uplifted channel remnants on the eastern rift flank of the Kerimbas Graben are indicative for this process. Since they were formed at least during the Late Miocene, they confirm Cenozoic tectonics to be responsible for the formation of the rift basin; (2) In contrast, active incision into the rift shoulder occurred in areas where the uplift rate of the shoulder is substantially lower than the downward erosion of the channel system. This is most likely the case for the southern part of the study area where a channel has incised deeply into the eastern rift shoulder. Based on these results, we established an evolutionary model for the interaction of tectonic activity and sediment routing systems of the Kerimbas Graben and adjacent southern areas, ranging from the Late Miocene to recent time